Urachal Diverticulum presenting as abdominal pain: a surprise at surgery - J., Chaithanya; B. K., Srinivas; K. S., Hanumanthaiah; S., Rajagopalan (International Surgery Journal, 2017)
A urachal diverticulum is one of the spectrum of presentation of urachal pathology, all of which are very rare in adulthood. This report describes the experience of a urachal diverticulum in adult. Urachal abnormalities result from incomplete regression of the fetal urachus. They are more common in children than in adults, due to urachal obliteration in early infancy.